Peran konselor dalam mengoptimalkan potensi siswa berbakat melalui layanan bimbingan dan konseling - Lilih Witjati; Radhyatul Hamidah (Universitas Negeri Padang, 2023)
Gifted students are students who have superior abilities or potential and can provide high achievements, have above average intelligence, creativity and development of abilities above average. These gifted students have special needs in order to support their potential to develop. Gifted children by nature have a need to develop and grow optimally, so they need meaningful help from adults around them, both parents or teachers. This research uses literature study method from various sources. With the aim of examining the role of counselors in optimizing the potential of gifted students through guidance and counseling services. Data collection techniques using a review study of books, literatures, notes and reports related to the problem being solved. The author uses various literatures such as books, journals and other relevant references related to the need in writing articles on the role of counselors in optimizing the potential of gifted students through guidance and counseling services. Thus, school counselors are able to play an active role in developing the potential of gifted students. A qualified school counselor is able to provide guidance and counseling services that will later guide, direct and encourage the development of the potential of gifted students optimally.